1995
DOI: 10.1079/bjn19950007
|View full text |Cite
|
Sign up to set email alerts
|

Passage rate and total clearance rate from the rumen of cows fed on grass silages differing in cell-wall content

Abstract: Four non-lactating, rumen-fistulated cows were fed ad lib. on two grass silages (first cut (FC) and second cut (SC)) harvested at different growth stages, resulting in different crude-protein (CP) and neutraldetergent-fibre (NDF) contents (FC, 152 g CP/kg, 515 g NDF/kg and SC, 210 g CP/kg, 442 g NDF/kg). Voluntary intake and rumen contents, total as well as organic matter were higher for silage FC. Fractional passage rate from the rumen, calculated from the logarithmic decline in Cr-NDF rumen pool, was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 11 publications
5
15
0
Order By: Relevance
“…However, TMRT of Cr-NDF was comparable throughout all passage studies cited despite qualitative contrasts of the diets used. These results suggest that Cr-NDF is less sensitive to dietary changes than 13 C. This is in line with Bosch and Bruining (1995) who concluded that Cr-NDF ground to 0.2-1.0 mm associates to the small indigestible rumen particle pool and can be considered to be only representative of that specific pool. In contrast, 13 C isotopes, incorporated as natural components in all plant components, represent the entire fraction in which they are analytically recovered and better suitable to measure differences between diets.…”
Section: Accuracy Of Curve Fitssupporting
confidence: 89%
See 1 more Smart Citation
“…However, TMRT of Cr-NDF was comparable throughout all passage studies cited despite qualitative contrasts of the diets used. These results suggest that Cr-NDF is less sensitive to dietary changes than 13 C. This is in line with Bosch and Bruining (1995) who concluded that Cr-NDF ground to 0.2-1.0 mm associates to the small indigestible rumen particle pool and can be considered to be only representative of that specific pool. In contrast, 13 C isotopes, incorporated as natural components in all plant components, represent the entire fraction in which they are analytically recovered and better suitable to measure differences between diets.…”
Section: Accuracy Of Curve Fitssupporting
confidence: 89%
“…Recent studies further emphasised the advantages of stable isotopes in estimating feed-specific fractional passage rates (Huhtanen and Hristov, 2001;Pellikaan et al, 2013). In the latter study, 13 C-labelled grass silage yielded lower fractional rumen passage rates compared to the external marker chromium-mordanted fibre (Cr-NDF), likely because the latter marker typically associates to the small indigestible rumen particle pool (Bosch and Bruining, 1995). Such marker discrepancies were also reported between Cr-NDF and the internal marker NDF following rumen evacuations (Robinson et al, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…This is in contrast with Bruining et al (1998) using grass, maize and lucerne silages and Huhtanen et al (2007) using timothy hay. However, the present results are consistent with the data reported by Bosch et al (1992) and Bosch and Bruining (1995), who observed that the small particle fraction was larger than the large particle fraction with grass silage based diets.…”
Section: Particle Distribution Ndf and Indf Concentrations And Rumensupporting
confidence: 83%
“…DM, NDF or starch), and therefore may behave differently with regard to passage, and are maybe only representative for the fraction of feed particles with a size and density similar to that of the marker (Bruining and Bosch, 1992). Compared with work conducted with external markers (Colucci et al, 1990;Bosch and Bruining, 1995;Rinne et al, 1997), the 13 C-DM and especially the 13 C-NDF appear to yield lower fractional passage rates. This indicates that the external marker as used in the current trial (Cr-NDF, ground at 0.5 mm) may overestimate the fractional passage rate of the internal marker (cut at 3 cm), in particular that of the NDF fraction.…”
mentioning
confidence: 96%